Habitat‐specific behavior, growth rate, and survival of piping plover chicks in New Jersey, USA. Issue 10 (11th October 2021) - Stantial, Michelle L.; Cohen, Jonathan B.; Darrah, Abigail J.; Farrell, Shannon; Maslo, Brooke
Abstract: Anthropogenic disturbance has been demonstrated to affect the behavior of beach‐nesting birds, yet the energetic consequences of recreational activities have received less attention. Because precocial chicks are often displaced as a result of disturbance events, lower access to food may lead to lower fitness. We studied the influence of site characteristics and human disturbance on behavior, habitat use, growth rate, and survival of piping plover chicks in New Jersey, a portion of the Atlantic Coast population that continues to demonstrate poor demographic output. Sites varied in levels of human disturbance and access to high‐quality foraging habitat, which are two critical components of fledging success. We found that compared to chicks with access to bayside foraging habitat, chicks at sites without such access experienced higher rates of anthropogenic disturbance, spent less time in moist‐substrate habitats, and spent more time in upland dunes. Foraging rates were greatest for chicks in moist‐substrate habitat with bayside access and for chicks in the oceanside intertidal zone without bayside access. Further, overall chick growth rates were higher for chicks reared at sites with bayside access. Chick survival increased with age, decreased with increasing precipitation, and increased with bayside foraging habitat availability. Human disturbance was likely limiting chick access to foraging opportunities at sites open to the public, with an apparent effect on growth rate. Maintaining access to high‐quality foraging habitat that is free of human activity through habitat restoration, supplementary food, or beach closures could help to increase reproductive success in New Jersey.